2014
DOI: 10.3389/fimmu.2014.00151
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Models to Study Dengue Virus Immunology and Pathogenesis

Abstract: The development of a compelling murine model of dengue virus (DENV) infection has been challenging, because DENV clinical isolates do not readily replicate or cause pathology in immunocompetent mice. However, research using immunocompromised mice and/or mouse-adapted viruses allows investigation of questions that may be impossible to address in human studies. In this review, we discuss the potential strengths and limitations of existing mouse models of dengue disease. Human studies are descriptive by nature; m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
78
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(80 citation statements)
references
References 139 publications
2
78
0
Order By: Relevance
“…However, some DENV strains replicate in IFNAR Ϫ/Ϫ mice to detectable levels (47), which allows for assessment of the effect of priming on subsequent DENV challenge. Those experiments would be impossible in wildtype (WT) mice in which DENV does not replicate to measurable levels (47). Consistent with results obtained from experiments using AG129 mice, homotypic priming with 1 ϫ 10 6 PFU DENV2 (strain PL046) 2 weeks prior to DENV2 challenge (2 ϫ 10 5 PFU, strain S221) reduced viral RNA titers in the livers of IFNAR Ϫ/Ϫ mice upon challenge, even when CD8 ϩ T cells were depleted before challenge (Fig.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…However, some DENV strains replicate in IFNAR Ϫ/Ϫ mice to detectable levels (47), which allows for assessment of the effect of priming on subsequent DENV challenge. Those experiments would be impossible in wildtype (WT) mice in which DENV does not replicate to measurable levels (47). Consistent with results obtained from experiments using AG129 mice, homotypic priming with 1 ϫ 10 6 PFU DENV2 (strain PL046) 2 weeks prior to DENV2 challenge (2 ϫ 10 5 PFU, strain S221) reduced viral RNA titers in the livers of IFNAR Ϫ/Ϫ mice upon challenge, even when CD8 ϩ T cells were depleted before challenge (Fig.…”
Section: Resultssupporting
confidence: 82%
“…To evaluate the effect of nonlethal DENV priming on a subsequent lethal challenge with a different DENV serotype (heterotypic challenge) shortly after priming, we first used a model of DENV infection in 129/Sv mice lacking type I and II IFN receptors (AG129 mice). We chose this model because some DENV strains replicate in AG129 mice and cause a disease that recapitulates many features of DENV infection in humans and can be lethal (39,41,46,47). AG129 mice were nonlethally primed with 1 ϫ 10 4 PFU DENV4 (strain H241) 2 weeks prior to challenge with 1 ϫ 10 5 PFU DENV2 (strain S221), and survival was monitored.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…34 Previous studies showed that intradermal inoculation of a wide range of DENV doses (4 9 10 7 to 3 9 10 9 PFU/mouse) in mice caused different levels of haemorrhage and thrombocytopenia. 25 Using this model in our study (1 9 10 9 DENV PFU/mouse), we found that Kit W-sh/W-sh mice are more susceptible to intradermal DENV infection than WT mice, as indicated by increased NS3 staining at the skin inoculation site.…”
Section: Discussionmentioning
confidence: 99%
“…Mice are widely used as an animal model to study flavivirus pathogenicity and antiviral tests (29)(30)(31). To this end, we systematically characterized the neurovirulence and neuroinvasiveness of DTMUV in mice.…”
Section: Discussionmentioning
confidence: 99%